2019
DOI: 10.1002/edm2.101
|View full text |Cite
|
Sign up to set email alerts
|

Circadian‐timed quick‐release bromocriptine lowers elevated resting heart rate in patients with type 2 diabetes mellitus

Abstract: Objective: Sympathetic nervous system (SNS) overactivity is a risk factor for insulin resistance and cardiovascular disease (CVD). We evaluated the impact of bromocriptine-QR, a dopamine-agonist antidiabetes medication, on elevated resting heart rate (RHR) (a marker of SNS overactivity in metabolic syndrome), blood pressure (BP) and the relationship between bromocriptine-QR's effects on RHR and HbA1c in type 2 diabetes subjects.Design and Subjects: RHR and BP changes were evaluated in this post hoc analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 145 publications
2
14
0
Order By: Relevance
“…A total of 3456 participants were randomized and 3433 were included in the final analyses. Of the included participants, 3070 originated from the CST conducted by Gaziano et al 41,42 Nine of the trial reports included in the qualitative analysis reported results from the CST 10,32,34–36,39–42 . The trial conducted by Gaziano et al included all 3070 randomized participants in its final analysis, hence this trial report was included in the meta analysis 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3456 participants were randomized and 3433 were included in the final analyses. Of the included participants, 3070 originated from the CST conducted by Gaziano et al 41,42 Nine of the trial reports included in the qualitative analysis reported results from the CST 10,32,34–36,39–42 . The trial conducted by Gaziano et al included all 3070 randomized participants in its final analysis, hence this trial report was included in the meta analysis 41 .…”
Section: Resultsmentioning
confidence: 99%
“…An additional two records were identified by searching the reference lists of included trials and reviews. As illustrated in the PRISMA flow diagram (Appendix S1), 28 17 publications [10][11][12][29][30][31][32][33][34][35][36][37][38][39][40][41][42] reporting the effect of bromocriptine or cabergoline on T2D in nine trials 11,12,[29][30][31]33,37,38,41 were identified. A total of 3456 participants were randomized and 3433 were included in the final analyses.…”
Section: Bibliographical Search and Trial Characteristicsmentioning
confidence: 99%
“…Such activities in turn stimulate vascular iNOS and NADPH oxidase 4, thus generating ROS/RNS that lead to more vascular inflammation, cellular damage, and matrix remodeling, and ultimately vascular disease as outlined above. Among these pathological neuroendocrine factors, elevated sympathetic tone stands out as a singular pathology that can itself potentiate the entire metabolic syndrome and vascular disease thereof (reviewed in [ 12 ]). Bromocriptine administration at ZT 13 has previously been demonstrated to ameliorate the obese, hyperinsulinemic-insulin-resistant state with concurrent reductions in elevated sympathetic tone, hypertension, liver inflammatory cytokine transcription factor production, liver fat content, and hyperleptinemia in SHR rats on regular chow [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bromocriptine-QR is a unique quick release formulation of micronized bromocriptine, a potent dopamine D2 receptor agonist, which is FDA-approved to treat type 2 diabetes (T2D), indicated to be administered within 2 h of waking in the morning (the onset of daily locomotor activity and the natural peak of CNS dopaminergic activity) [ 12 ]. This circadian dopamine agonist therapy for type 2 diabetes provides only a brief morning pulse of dopamine agonist to the circulation, and yet reduces postprandial hyperglycemia across the three major meals of the day (i.e., up to 12 h after its administration) without raising the plasma insulin level [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 In an analysis of the relationship between resting heart rate (RHR) and the effect of dopamine agonist treatment on glycemia, 243 persons with RHR ≥ 70 receiving rapidly absorbed bromocriptine in the morning were compared with 129 receiving placebo, showing a significantly greater reduction in pulse with active treatment, which correlated with reduction in HbA1c, suggesting that elevated sympathetic nervous system tone, perhaps secondary to insulin resistance, is present in a subset of persons with type 2 diabetes and may be involved in the maintenance of hyperglycemia. 5 In a meta-analysis of six randomized controlled trials of the dopamine agonist bromocriptine enrolling 3339 participants and of three trials of cabergoline 0.5 mg enrolling 117 participants, both led to similar 0.7% reduction in HbA1c 6 ; this class of agents may deserve greater use. In a propensity score-matched analysis of 105 130 persons not having diagnosed cardiovascular disease (CVD) or CKD receiving SGLT2i and the same number treated with a DPP-4i, the former agents were associated with 29% lower likelihood of heart failure (HF), 56% lower likelihood of CKD, and 33% and 39% lower likelihood of all-cause and CV death; but no differences in stroke or myocardial infarction (MI).…”
Section: Insulin Resistance and Obesitymentioning
confidence: 99%